(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
TiO2 nanoparticles were prepared via sol-gel technique and then doped with cobalt ions to form TiO2 doped cobalt sol. Thin films were prepared from this sol using dip coating method and underwent calcination at a temperature of 550 C.The films were characterized by UV–Vis spectroscopy, X-ray diffraction (XRD), and atomic force microscopy (AFM). The UV–Vis. Absorption spectra show a redshift, which indicates that TiO2 doped cobalt will respond to the visible region of the spectrum rather than UV- region for pure TiO2.